Blockchain Interoperability Protocols: Bridging Multi-Chain Communication for Scalable Web3 Solutions (Blockchain, Web3 & Digital Trust Journal p-ISSN 3117-597X and e-ISSN 3117-5988, 2025)
The exponential growth of blockchain networks has fostered innovation across decentralized finance (DeFi), supply chain management, and digital identity ecosystems. However, the isolation of individual blockchains limits data and asset exchange, creating a fragmented Web3 environment. Blockchain interoperability—the ability of diverse blockchain systems to interact seamlessly—has emerged as a critical solution for scalability, liquidity, and global adoption. This research paper explores interoperability protocols such as Polkadot, Cosmos, Chainlink CCIP, and LayerZero, comparing their architectures, consensus mechanisms, and data relay models. Through comprehensive analysis and a case study approach, the study evaluates the performance, security, and scalability of these frameworks in multi-chain communication. Findings suggest that hybrid interoperability models combining decentralized relayers, trust-minimized bridges, and cryptographic proofs offer the most promising path toward a truly interconnected Web3 ecosystem